Active components of Solanum nigrum and their antitumor effects: a literature review - Zhang, Han; Lv, Jun-lin; Zheng, Qiu-sheng; Li, Jie (Frontiers in Oncology, 2023)
Cancer poses a serious threat to human health and overall well-being. Conventional cancer treatments predominantly encompass surgical procedures and radiotherapy. Nevertheless, the substantial side effects and the emergence of drug resistance in patients significantly diminish their quality of life and overall prognosis. There is an acute need for innovative, efficient therapeutic agents to address these challenges. Plant-based herbal medicines and their derived compounds offer promising potential for cancer research and treatment due to their numerous advantages. Solanum nigrum (S. nigrum), a traditional Chinese medicine, finds extensive use in clinical settings. The steroidal compounds within S. nigrum, particularly steroidal alkaloids, exhibit robust antitumor properties either independently or when combined with other drugs. Many researchers have delved into unraveling the antitumor mechanisms of the active components present in S. nigrum, yielding notable progress. This literature review provides a comprehensive analysis of the research advancements concerning the active constituents of S. nigrum. Furthermore, it outlines the action mechanisms of select monomeric anticancer ingredients. Overall, the insights derived from this review offer a new perspective on the development of clinical anticancer drugs.